2021
DOI: 10.1371/journal.pone.0248342
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive molecular characterization of the 8q22.2 region reveals the prognostic relevance of OSR2 mRNA in muscle invasive bladder cancer

Abstract: Technological advances in molecular profiling have enabled the comprehensive identification of common regions of gene amplification on chromosomes (amplicons) in muscle invasive bladder cancer (MIBC). One such region is 8q22.2, which is largely unexplored in MIBC and could harbor genes with potential for outcome prediction or targeted therapy. To investigate the prognostic role of 8q22.2 and to compare different amplicon definitions, an in-silico analysis of 357 patients from The Cancer Genome Atlas, who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The amplification of this region, and specifically E2F3 in bladder cancer, was associated with tumor cell proliferation [26]. The other three amplified regions in chromoanagenesis BLCA were also previously linked to bladder cancer; 1q23 [27], 3p25 [28], and 8q22 [29].…”
Section: Chromoanagenesis Cna Pattern Overlaps With Existing Knowledgementioning
confidence: 86%
“…The amplification of this region, and specifically E2F3 in bladder cancer, was associated with tumor cell proliferation [26]. The other three amplified regions in chromoanagenesis BLCA were also previously linked to bladder cancer; 1q23 [27], 3p25 [28], and 8q22 [29].…”
Section: Chromoanagenesis Cna Pattern Overlaps With Existing Knowledgementioning
confidence: 86%
“…LncRNA promotes urothelial cell proliferation and inhibits apoptosis through the molecular signaling pathway, which leads to the transformation of malignant degree. Therefore, lncRNA regulated progress of bladder cancer may become a biomarker for the diagnosis and prognosis of bladder cancer (7). Previous studies reported that the expression of lncRNA upregulated gene factor 1 (UBC1) in bladder cancer tissue was up-regulated by microarray and qRT-PCR technology, and the siRNA technique found that knockout UBC1 could inhibit the metastasis of bladder cancer cells (8,9).…”
Section: Introductionmentioning
confidence: 99%